Governing Health in High-Risk Bureaucracies: Institutional Misalignment and Reactive Policy Implementation in the Indonesian National Police - Niken Manohara; Triyuni Soemartono; T. Herry Rachmatsyah; Gatot Hery Djatmiko (Baileo: Jurnal Sosial Humaniora, 2026)
This study examines the institutional governance of occupational health within high-risk law enforcement institutions through a case study of the Indonesian National Police (INP), focusing on the misalignment between formal policy design and reactive implementation practices. Despite regulatory mandates such as the Chief of Police Regulation No. 7/2013 requiring periodic health screenings, participation remains low (24–26%), while high-risk classifications have tripled within a year. Using a qualitative case study approach, institutional screening data and medical records from the Jakarta Metropolitan Police (Polda Metro Jaya) were analyzed through documentary and thematic content analysis guided by Matland’s ambiguity–conflict model and policy implementation theory. The findings reveal that bureaucratic quota systems, weak digital infrastructure, and the absence of leadership accountability mechanisms undermine preventive health outcomes, leading to rising chronic diseases, preventable deaths, and declining institutional resilience. The study identifies systemic governance failures driven by compliance-oriented routines and proposes four reforms: risk-adaptive screening protocols, centralized digital health integration, leadership accountability metrics, and cross-sectoral preventive care partnerships. The novelty of this research lies in exposing institutional misalignment in police health governance, an underexplored area in Indonesian bureaucratic sociology, while extending the New Public Service paradigm to occupational health governance. Conceptually, it contributes to institutional sociology by linking policy rationality with frontline implementation behavior in high-risk public sectors.